THE TIDAL/DIURNAL CYCLES OF THE NUTRIENTS EVOLUTION FOR MICROPHYTOBENTHOS ACTIVITY - J-H. Lim; S. N. Longphuirt; A. Leynaert; P. Claquin; C-H. Koh; B-O. Kwon; S. An (International Association of Lowland Technology, 2009)
The objectives of this study were to investigate, the evolution of porewater nutrients in intertidal sediments over tidal and diurnal cycles, and the concentrations of nutrients to which the microphytobenthos are exposed during their vertical migration in the sediment. While porewater concentrations and their oscillation over tidal cycles have previously been measured, in our study we have included a high sampling frequency (2 hours) over a 2 day period. The tidal/diurnal cycle of dissolved inorganic nitrogen (nitrate+nitrite, ammonium), microphytobenthic biomass (Chl-a) and environmental parameters (temperature, light intensity, water depth) were studied on an intertidal flat in the Nakdong River estuary. We showed clear evolutions in the two nutrients which were significantly linked to the tidal cycle. Nitrate+nitrite showed an increasing trend in all depths during submersion periods, in contrast ammonium decreased, this resulted from the varying influence of diffusion and advection of overlying water. The microphytobenthos showed a normal migratory rhythm linked to the tidal cycle. Our result suggests that the evolution of porewater nutrients is mainly influenced by tidal cycle and the MPB activity may influence the nutrients evolution during emersion periods.